2006
DOI: 10.1037/0022-0167.53.3.379
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ethnic identity and gender role attitudes to the development of career choice goals among black and Latina girls.

Abstract: This study is a preliminary exploration of how individual differences in gender role attitudes and ethnic identity might be related to career decision self-efficacy and the gender traditionality of career choice goals in a sample of 102 9th-grade Black and Latina girls. Extending social-cognitive career theory, the authors examined 2 path models in which career decision self-efficacy mediated the effects of gender role attitudes and ethnic identity on the traditionality of the participants' career choice goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 39 publications
7
54
2
Order By: Relevance
“…Gloria and Hird () reported Cronbach's alphas of .95 and .97, respectively, for CDSE among 589 White and 98 undergraduate students of color. Gushue and Whitson () reported an alpha coefficient of .86 for CDSE in a sample of ninth‐grade Latinas (46.2%) and Black girls (51.9%). Reliability analysis for the present study revealed an alpha of .95 for the total CDSES‐SF scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gloria and Hird () reported Cronbach's alphas of .95 and .97, respectively, for CDSE among 589 White and 98 undergraduate students of color. Gushue and Whitson () reported an alpha coefficient of .86 for CDSE in a sample of ninth‐grade Latinas (46.2%) and Black girls (51.9%). Reliability analysis for the present study revealed an alpha of .95 for the total CDSES‐SF scale.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies have indicated that SCCT is useful in exploring the career paths of people of color (Flores & O'Brien, ; Gushue, ; Gushue & Whitson, ; Navarro, Flores, & Worthington, ). SCCT is based on Bandura's () social‐cognitive theory in which cognitive processes and social context are emphasized to explain learning and behavior.…”
mentioning
confidence: 99%
“…Germeijs and Verschueren (2009) also noted the importance of mothers' support in adolescents' career development, finding that a secure relationship with the mother also predicted more in-depth career exploration. Similarly, Gushue and Whitson (2006) linked parental support to higher career decision self-efficacy and outcome beliefs in adolescents, suggesting that positive support helps them overcome perceived barriers.…”
Section: Family Influence On Work and Careermentioning
confidence: 98%
“…Girls' career choice goals [1] and women's labor market experience [2] and monetary earnings [3] are heavily shaped by their gender role attitudes. In addition, gender role attitudes have some bearing on women's exposure to violence.…”
Section: Everything's Better In Moderation: Young Women's Gender Rolementioning
confidence: 99%